2021
DOI: 10.1007/s10311-021-01323-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 variants and environmental effects of lockdowns, masks and vaccination: a review

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is continuously evolving and four variants of concern have been identified so far, including Alpha, Beta, Gamma and Delta variants. Here we review the indirect effect of preventive measures such as the implementation of lockdowns, mandatory face masks, and vaccination programs, to control the spread of the different variants of this infectious virus on the environment. We found that all these measures have a considerable environmental impact, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The inadvertently indirect environmental factors, such as low emission of air pollution, low-density population, tropical weather in summer season, and the rural areas between the coast and the mountains, might be minor factors that helped to stop the Pingtung Delta-SARS-CoV-2 outbreak within 1 month. The previ-ous study reported that indirectly preventive measures like mandatory face masks, the implementation of lockdown leading to restriction of human activities and improvement of air quality, and vaccination is probably limited for the spread of the different SARS-CoV-2 variants [36]. No new COVID-19 cases including Omicron were found in Pingtung after the end of the Pingtung Delta-variant outbreak (5 July, 2021) until the present (27 January, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The inadvertently indirect environmental factors, such as low emission of air pollution, low-density population, tropical weather in summer season, and the rural areas between the coast and the mountains, might be minor factors that helped to stop the Pingtung Delta-SARS-CoV-2 outbreak within 1 month. The previ-ous study reported that indirectly preventive measures like mandatory face masks, the implementation of lockdown leading to restriction of human activities and improvement of air quality, and vaccination is probably limited for the spread of the different SARS-CoV-2 variants [36]. No new COVID-19 cases including Omicron were found in Pingtung after the end of the Pingtung Delta-variant outbreak (5 July, 2021) until the present (27 January, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there are reports that both indoor and outdoor air pollution increase the risk of SARS-CoV-2 infection and its cardiovascular complications (Ali and Islam 2020 ). On the other hand, there is evidence that preventive measures to reduce the spread of SARS-CoV-2 can be a source of environmental pollution, including air pollution, and have adverse health effects (Akter et al 2021 ; Ufnalska and Lichtfouse 2021 ).…”
Section: Associations Between Chronic Ambient Air Pollution and Cardi...mentioning
confidence: 99%
“…Like other RNA viruses, SARS-CoV-2 has very high mutation rates (Akter et al 2021 ; Dai et al 2020 ; Duffy 2018 ; Wu et al 2021 ). To date, a total of 407 pango lineages of SARS-CoV-2 variants have been identified (Nextstrain 2021 ).…”
Section: What Next After the Delta Variant?mentioning
confidence: 99%
“…It was concluded that, although their effectiveness rates decreased to some extent, the current vaccines developed for SARS-CoV-2 still provide considerable protection against the Delta variant. Like other RNA viruses, SARS-CoV-2 has very high mutation rates (Akter et al 2021;Dai et al 2020;Duffy 2018;Wu et al 2021). To date, a total of 407 pango lineages of SARS-CoV-2 variants have been identified (Nextstrain 2021).…”
Section: Effectiveness Of Current Vaccines On the Delta Variantmentioning
confidence: 99%